Perancangan Ui/Ux Aplikasi Sumatera Bus Berbasis Android Menggunakan Figma - Alda, Muhamad; Daulay, Nurul Arfisyah; Khoiriah, Erni; Berutu, Mira Pebriani (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sumatera Bus is an android application for ordering bus tickets online. In the process of ordering tickets manually, various obstacles often occur, including running out of bus tickets. The process of ordering manual tickets became the basis for making the Sumatera Bus android application. With the presence of Sumatera Bus, it is expected that the process of buying tickets will run smoothly for prospective passengers and a wider range of business for the management of Sumatera Bus. The methodology used for system design is the prototyping methodology. System design using figma and visual appearance with user interface and user experience. The results of this research are expected to be able to develop the Sumatera Bus business market and provide convenience for prospective passenger in ordering tickets so as to provide a good travel experience. Keywords: Android, UI/UX, Prototype, Bus, Figma.